Contribution of individual components of a job cycle on overall severity of whole-body vibration exposure: a study in Indian mines. Issue 1 (2nd January 2016) - Mandal, Bibhuti B.; Mansfield, Neil J.
Abstract : Drivers of earth-moving machines are exposed to whole-body vibration (WBV). In mining operations there can be a combination of relatively high magnitudes of vibration and long exposure times. Effective risk mitigation requires understanding of the main aspects of a task that pose a hazard to health. There are very few published studies of WBV exposure from India. This paper reports on a study that considered the contribution of the component phases of dumper operations, on the overall vibration exposure of the drivers. It shows that vibration magnitudes are relatively high, and that haulage tasks are the main contributor to the exposure. It is recommended that driver speed, haul road surfaces and vehicle maintenance/selection are optimized to ensure minimization of vibration. If this is not sufficient, operation times might need to be reduced in order to ensure that the health guidance caution zone from Standard No. ISO 2631-1:1997 is not exceeded.